2005
DOI: 10.1002/pmic.200400941
|View full text |Cite
|
Sign up to set email alerts
|

Housekeeping proteins: A preliminary study illustrating some limitations as useful references in protein expression studies

Abstract: A primary objective of many protein expression studies is to define expression patterns that can distinguish between normal and diseased states, enabling a better understanding of molecular events associated with disease development and progression and ultimately potentially finding novel markers or therapeutic targets. Exploration and confirmation of many proteins is often done using Western blotting with normalization against "housekeeping proteins", such as glyceraldehyde-3-phosphate dehydrogenase (GAPDH), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
182
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(196 citation statements)
references
References 28 publications
7
182
0
2
Order By: Relevance
“…Concentrations of mRNA are expressed relative to the level of b-actin. Even though Ferugson et al [15] showed the higher expression of b-actin in RCC, it was marginal. Statistical significance of differences between mean values was calculated using the paired t-test and a p,0.05 (two-tailed) was considered to be significant.…”
Section: Quantitative Real Time Rt-pcrmentioning
confidence: 90%
“…Concentrations of mRNA are expressed relative to the level of b-actin. Even though Ferugson et al [15] showed the higher expression of b-actin in RCC, it was marginal. Statistical significance of differences between mean values was calculated using the paired t-test and a p,0.05 (two-tailed) was considered to be significant.…”
Section: Quantitative Real Time Rt-pcrmentioning
confidence: 90%
“…GLUT4 content was expressed in arbitrary units per microgram of applied protein, considering the mean of control animals 100%. Protein-loaded content was confirmed by analyzing posttransferring Coomassie-stained gels (Ferguson et al 2005). …”
Section: Methodsmentioning
confidence: 99%
“…A standard curve with 2, 4, 6, 8, and 10 mg of bovine serum albumin (A4503, Sigma Chemicals, St Louis, MO, USA) was drawn for each dosing run. As housekeeping proteins (such as a-actin and b-tubulins) are sensitive to experimental treatments (particularly pharmacologic treatments) and to diverse physiological conditions and have therefore some limitations as internal standard (Ferguson et al, 2005), 3-6 measurements were made for each brain region of each animal; to minimize procedural variables, homogenates from treated and control animals LY379268 blocks CEF-induced PPI impairment M Bellesi and F Conti were loaded onto the same gel (Bragina et al, 2006). For a semi-quantitative analysis, we drew standard curves of increasing concentration of total protein from controls (n ¼ 4) to define a linear range for immunoblot densitometric analysis (Bragina et al, 2006).…”
Section: Western Blottingmentioning
confidence: 99%